Too Big NOT to Fail. - HELLAND, PAT; WEAVER, SIMON; HARRIS, ED (Communications of the ACM, 2017)
The article discusses techniques for Web-scale computing in relation to autonomous operation of server infrastructure. Topics include the nature of Web-scale datacenters, the nature of operations in relation to server staff, and the nature of software for the stateless servers used as Web-scale. The deployment and testing of software at Web-scale is addressed.